1982
DOI: 10.3109/01902148209115817
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Tracheal Goblet Cell Ultrastructure: A Three-Dimensional Reconstruction

Abstract: In order to study specific anatomical relationships among organelles involved in the movement and secretion of mucin granules by airway epithelium, a three-dimensional replica of a single goblet cell from porcine trachea was constructed by means of transmission electron microscopy of serially prepared ultrathin sections. Many features of the goblet cell that could not be deduced from single planes of section were revealed. The cell is columnar in configuration. The cytoplasm contains not one, but several discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…These granules vary in their morphologic and histochemical properties. Three-dimensional reconstruction of mucous goblet cells showed that this variation reflects different stages of mucous cell secretion (Adler et al, 1982). Similarly, the apical surface of mucus cells varies with the stage of secretion.…”
Section: Secretory Cellsmentioning
confidence: 94%
“…These granules vary in their morphologic and histochemical properties. Three-dimensional reconstruction of mucous goblet cells showed that this variation reflects different stages of mucous cell secretion (Adler et al, 1982). Similarly, the apical surface of mucus cells varies with the stage of secretion.…”
Section: Secretory Cellsmentioning
confidence: 94%
“…This result indicates a clear difference in airway epithalial tissue organization of indoor reared pigs compared to outdoor reared pigs. The cytoplasm of porcine tracheal goblet cells contains several clusters of mucin granules (Adler et al, 1982); mucin is the protein component of mucus. The airway epithelium is a dynamic tissue capable of undergoing reversible cellular adaptations, including goblet cell hyperplasia, in response to a myriad of stimuli (Chen et al, 1991;Rock et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This cell type is characterized by the presence of numerous large glycoprotein-containing secretory granules. The supranuclear cytoplasm of goblet cells is filled with secretory granules, and the nucleus is located at the cell base (Adler et al 1982;Basbaum et al 1988;Furuya et al 1998).…”
Section: Introductionmentioning
confidence: 99%